2009
DOI: 10.1245/s10434-009-0452-2
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Developing Arm Lymphedema Among Breast Cancer Survivors: A Meta-Analysis of Treatment Factors

Abstract: Mastectomy, extent of axillary dissection, radiation therapy, and presence of positive nodes increased risk of developing arm lymphedema after breast cancer. These factors likely reflected lymph node removal, which most surgeons consider to be the largest risk factor for lymphedema. Future studies should consider examining sentinel node biopsy versus no dissection with a long follow-up time post surgery to see if there is a benefit of decreased lymphedema compared with no dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
251
2
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(267 citation statements)
references
References 90 publications
7
251
2
7
Order By: Relevance
“…Además, varios estudios han demostrado que la posterior RT, especialmente cuando se irradia la zona axilar, genera cambios en el drenaje del MS, que son más tardíos que los de la propia cirugía, pero que agravan la insuficiencia linfática debido a la fibrosis post-radiación (29,37,46). Puede aparecer tanto tras una LA cómo tras una BSGC (es más frecuente tras la LA), debido a la interrupción quirúrgica de algunas de las vías linfáticas superficiales que drenan tanto la mama como el MS; además de la disección de los ganglios linfáticos.…”
Section: Secuelas Derivadas De Los Tratamientosunclassified
“…Además, varios estudios han demostrado que la posterior RT, especialmente cuando se irradia la zona axilar, genera cambios en el drenaje del MS, que son más tardíos que los de la propia cirugía, pero que agravan la insuficiencia linfática debido a la fibrosis post-radiación (29,37,46). Puede aparecer tanto tras una LA cómo tras una BSGC (es más frecuente tras la LA), debido a la interrupción quirúrgica de algunas de las vías linfáticas superficiales que drenan tanto la mama como el MS; además de la disección de los ganglios linfáticos.…”
Section: Secuelas Derivadas De Los Tratamientosunclassified
“…Of the included reviews, thirteen reported challenges faced by bca patients and survivors [27][28][29][30][31][32][33][34][35][36][37][38]40 . Their findings are categorized and described next.…”
Section: Cancer-or Cancer Treatment-related Challengesmentioning
confidence: 99%
“…Two reviews reported on bca-related lymphedema 27,29 . One estimated the risk for lymphedema based on the treatment that the bca patients received, and they observed that the risk for lymphedema was higher in patients who underwent mastectomy than in those who underwent lumpectomy; higher in those who had an axillary dissection than in those who had no axillary dissection; higher in those who underwent axillary dissection than in those who had a sentinel lymph node biopsy; and higher in those who received radiation and in those who had positive axillary nodes than in those who did not.…”
Section: Lymphedemamentioning
confidence: 99%
“…A külső té-nyezők a következők lehetnek: műtét radikalitása (példá-ul eltávolított nyirokcsomók száma), műtéti vagy későb-bi szövődmények (például seroma, sebfertőzés, cellulitis), irradiáció vagy kemoterápia [3]. A belső tényezők közé tartoznak: a tumor stádiuma és számos egyéb nyirokö-démára hajlamosító kísérő betegség, mint obesitas, lipoedema, anyagcsere-betegségek, immobilizáció, szív-, vese-, májelégtelenség, krónikus tüdőbetegség stb.…”
Section: Kockázati Tényezőkunclassified